Non-Line-of-Sight Detection Based on Neuromorphic Time-of-Flight Sensing - Park, Minseong; Yuan, Yuan; Baek, Yongmin; Bae, Byungjoon; Park, Bo In; Kim, Young Hoon; Lin, Nicholas; Heo, Junseok; Lee, Kyusang (ACS Photonics, 2023)
Non-line-of-sight (NLOS) detection and ranging aim to identify hidden objects by sensing indirect light reflections. Although numerous computational methods have been proposed for NLOS detection and imaging, the post-signal processing required by peripheral circuits remains complex. One possible solution for simplifying NLOS detection and ranging involves the use of neuromorphic devices, such as memristors, which have intrinsic resistive-switching capabilities and can store spatiotemporal information. In this study, we employed the memristive spike-timing-dependent plasticity learning rule to program the time-of-flight (ToF) depth information directly into a memristor medium. By coupling the transmitted signal from the source with the photocurrent from the target object into a single memristor unit, we were able to induce a tunable programming pulse based on the time interval between the two signals that were superimposed. Here, this neuromorphic ToF principle is employed to detect and range NLOS objects without requiring complex peripheral circuitry to process raw signals. We experimentally demonstrated the effectiveness of the neuromorphic ToF principle by integrating a HfO2 memristor and an avalanche photodiode to detect NLOS objects in multiple directions. This technology has potential applications in various fields, such as automotive navigation, machine learning, and biomedical engineering.
Keywords: Hidden objects; Memristor; Neuromorphic; Neuromorphic computing; Nonline of sight; Peripheral circuits; Post signal processing; Resistive switching; Spike timing dependent plasticities; Time-of flight; avalanche photodiodes; memristors; neuromorphic computing; non-line-of-sight; spike-timing-dependent plasticity; time-of-flight